1995
DOI: 10.1159/000264226
|View full text |Cite
|
Sign up to set email alerts
|

Current Maternal Age Recommendations for Prenatal Diagnosis: A Reappraisal Using the Expected Utility Theory

Abstract: The expected utility theory suggests eliminating an age-specific criterion for recommending prenatal diagnosis to patients. We isolate the factors which patients and physicians need to consider intelligently in prenatal diagnosis, and show that the sole use of a threshold age as a screening device is inadequate. Such a threshold fails to consider adequately patients’ attitudes regarding many of the possible outcomes of prenatal diagnosis; in particular, the birth of a chromosomally abnormal child and procedura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Although the continued reliance on the 35-year-old threshold has been questioned repeatedly over the years [7,20,31,[33][34][35] , it continues to be used. In the most recent (2001) American College of Obstetricians and Gynecologists (ACOG) 'Practice Bulletin' addressing prenatal diagnosis of fetal chromosomal abnormalities, women who will be aged 35 and older at the time of delivery are the fi rst-listed category of women who are 'at high risk' and should be offered diagnostic testing [36] .…”
Section: Current Prenatal Testing Guidelinesmentioning
confidence: 99%
“…Although the continued reliance on the 35-year-old threshold has been questioned repeatedly over the years [7,20,31,[33][34][35] , it continues to be used. In the most recent (2001) American College of Obstetricians and Gynecologists (ACOG) 'Practice Bulletin' addressing prenatal diagnosis of fetal chromosomal abnormalities, women who will be aged 35 and older at the time of delivery are the fi rst-listed category of women who are 'at high risk' and should be offered diagnostic testing [36] .…”
Section: Current Prenatal Testing Guidelinesmentioning
confidence: 99%
“…Since Down syndrome accounts for about half of the main fetal chromosomal defects that occur, the choice of a 1:250 cut-off risk of Down syndrome as a criterion for proposing amniocentesis is commonly justified by the argument that women should be offered an amniocentesis when the probability of having a child with a major chromosomal defect exceeds the probability of having a procedure-related miscarriage (Harris et al, 2004;Grobman et al, 2002;Kuppermann et al, 2000;Seror and Costet, 1998;Sicherman et al, 1995). While the implications of this argument are that women are assumed to perceive the birth of a child with a major chromosomal disorder as a health state equivalent to that of a miscarriage, many studies (including this one) have shown that women attach significantly higher utility values to the occurrence of miscarriage than to the birth of an affected child (Harris et al, 2004;Grobman et al, 2002;Kuppermann et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…These studies provide important findings, as pregnant women's trade‐offs between risks can then be compared with those leading to cut‐off risks for proposing invasive prenatal testing based on biochemical screening or NT measurement. The choice of cut‐off risks is indeed commonly based on equalization of risks of occurrence of outcomes that are supposed to be similarly valued, assuming that women should not be offered prenatal invasive testing when the probability of procedure‐related miscarriage exceeds the probability of having an affected child18–22.…”
Section: Outcomes and Decision‐makingmentioning
confidence: 99%